A Decade of Qur’anic Bibliotherapy Research: Google Scholar Visualization Study (2013–2023) - Hak, Ade Abdul; Maylaffayza, Hilya (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2025)
This study conducts a bibliometric analysis of Qur’anic bibliotherapy research trends indexed in Google Scholar from 2013 to 2023. Employing a descriptive quantitative approach, 53 articles were retrieved using the Publish or Perish application and analyzed with VOSviewer and ATLAS.ti to map authorship patterns, keyword clusters, and thematic developments. The findings reveal several dominant themes, including “Qur’an,” “anxiety,” “bibliotherapy,” and “depression,” while topics such as “teaching,” “attitude,” “impact,” and “child” remain relatively underexplored. The analysis also shows a steady increase in publication output over the decade, suggesting growing scholarly interest in the use of Qur’anic narratives as therapeutic interventions. This study underscores the value of bibliometric mapping for identifying research gaps and guiding future inquiry in Qur’anic bibliotherapy. By organizing existing knowledge, the research contributes to the development of more effective therapeutic practices and supports the integration of Qur’anic principles into mental health care.